2018
DOI: 10.3390/molecules23030560
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Purification of Two Isoflavones from Hericium erinaceum Mycelium by High-Speed Counter-Current Chromatography

Abstract: High-speed counter-current chromatography (HSCCC) was used to separate and purify two isoflavones for the first time from Hericium erinaceum (H. erinaceum) mycelium using a two-phase solvent system composed of chloroform-dichloromethane-methanol-water (4:2:3:2, v/v/v/v). These two isoflavones were identified as genistein (4′,5,7-trihydroxyisoflavone, C15H10O5) and daidzein (4′,7-dihydroxyisoflavone, C15H10O4), using infrared spectroscopy (IR), electro-spary ionisation mass (ESI-MS), 1H-nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…On comparing the economical aspect, the combined cost of industrial‐grade resin membranes and chromatography columns is less than the cost of manufacturing genistein chemically. Further, upcoming technologies such as high‐speed counter‐current chromatography (HSCCC) are being developed that eliminate the need for adsorption matrices for purified isolation of genistein, 44,45 thereby lowering the cost even more. The work detailed in this article thus holds substantial potential for industrial scale‐up studies, as a valuable cost‐efficient alternative resource for harnessing natural isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…On comparing the economical aspect, the combined cost of industrial‐grade resin membranes and chromatography columns is less than the cost of manufacturing genistein chemically. Further, upcoming technologies such as high‐speed counter‐current chromatography (HSCCC) are being developed that eliminate the need for adsorption matrices for purified isolation of genistein, 44,45 thereby lowering the cost even more. The work detailed in this article thus holds substantial potential for industrial scale‐up studies, as a valuable cost‐efficient alternative resource for harnessing natural isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse type structure of isoflavonoids was synthesized from flavanone, which have been reported several plants as corylifol A, neobavaisoflavone, and irisflorentin from Cytisus striatus [77], formoninetin and biochanin A from Hylastinus obscurus [78]. One new leptoisoflavone A (a rare 5-membered dihydrofuran ring) from Limonium leptophyllum [79], 2,2′-trimethoxy-6,8-dihydroxy-isoflavone from the ethanol extract of Thespesia populnea bark [80] and isoflavones, genistein and daidzein from Hericium erinaceum (Figure 9) [81]. from aerial parts of Chenopodium album [84], amurensin and cosmosiin from Trigonella foenum graecum [85], rhamnosides flavonol, kaempferol-3-O-rhamnoside and quercetin-3-O-rhamnoside from leaves of Pometia pinnata [86] and a new flavonol glycoside, sabiapside A from Sabia parviflora [87] (Figure 10).…”
Section: Isoflavonoidsmentioning
confidence: 99%
“…However, little was known about flavonoids, which were studied by separation and purification using a HSCCC method with a two-phase solvent system, namely chloroform–dichloromethane–methanol–water. With the aid of different spectroscopic and spectrometric techniques, including ESI-MS, He et al [53] identified daidzein and genistein in the fungus mycelium.…”
Section: Analysis Of Bioactive Compoundsmentioning
confidence: 99%